Pro-apoptotic Bax mRNA expression: A novel predictor for systemic lupus erythematosus disease flare-up - Rasha N Yousef,; Abeer Ramadan,; Eman Awadallah,; Alshaimaa R Alnaggar,; Noha M Khalil,; Mervat E.Behiry,; Asmaa Ali,; Hesham Gamal El Dine, (Archives of Rheumatology, 2023)
Objectives: In this study, we aimed to better understand the expression of pro-apoptotic Bad and Bax in the pathogenesis of systemic lupus erythematosus (SLE) and their relationship with the disease activity. Patients and methods: Between June 2019 and January 2021, a total of 60 female patients with SLE (median age 29 years; IQR, 25.0-32.0) and 60 age- and sex-matched healthy female controls (median age: 30 years; IQR, 24.0-32.0) were included. The Bax and Bad messenger ribonucleic acid (mRNA) expression was measured by real-time polymerase chain reaction. Results: The expression of Bax and Bad was significantly lower in SLE group than the control group. The median value of mRNA expression of Bax and Bad was 0.72 and 0.84, respectively versus 0.76 and 0.89 in the control group. The median value of (Bax*Bad)/β-actin index was 17.8 in the SLE group and 19.64 in the control group. The expression of both Bax, Bad and (Bax*Bad)/β-actin index had a good significant diagnostic utility (area under the curve [AUC]= 0.64, 0.70, and 0.65, respectively). The Bax mRNA expression showed a significant upregulation with disease flare-up. The efficacy of Bax mRNA expression in predicting SLE flare-up was good (AUC= 73%). In the regression model, the probability of flare-up reached 100%, with increasing Bax/β-actin as well, and the likelihood of flare-up increased 10,314 times with every unit increase of Bax/β-actin mRNA expression. Conclusion: Deregulation of the mRNA expression of Bax may have a role in the susceptibility to SLE and may be associated with disease flare. A better understanding of the expression of these pro-apoptotic molecules may carry a great potential for the development of specific effective therapies.